NMR Fingerprinting of Conventional and Genetically Modified Soybean Plants with AtAREB1 Transcription Factors - Coutinho, Isabel Duarte; Facchinatto, William Marcondes; Mertz-Henning, Liliane Marcia; Carvalho Viana, Americo Jose; Marin, Silvana Regina Rockenbach; Santagneli, Silvia Helena [UNESP]; Nepomuceno, Alexandre Lima; Colnago, Luiz Alberto (Amer Chemical Soc, 2024)
Drought stress impacts soybean yields and physiological processes. However, the insertion of the activated form of the AtAREB1 gene in the soybean cultivar BR16, which is sensitive to water deficit, improved the drought response of the genetically modified plants. Thus, in this study, we used 1H NMR in solution and solid-state NMR to investigate the response of genetically modified soybean overexpressing AtAREB1 under water deficiency conditions. We achieved that drought-tolerant soybean yields high content of amino acids isoleucine, leucine, threonine, valine, proline, glutamate, aspartate, asparagine, tyrosine, and phenylalanine after 12 days of drought stress conditions, as compared to drought-sensitive soybean under the same conditions. Specific target compounds, including sugars, organic acids, and phenolic compounds, were identified as involved in controlling sensitive soybean during the vegetative stage. Solid-state NMR was used to study the impact of drought stress on starch and cellulose contents in different soybean genotypes. The findings provide insights into the metabolic adjustments of soybean overexpressing AREB transcription factors in adapting to dry climates. This study presents NMR techniques for investigating the metabolome of transgenic soybean plants in response to the water deficit. The approach allowed for the identification of physiological and morphological changes in drought-resistant and drought-tolerant soybean tissues. The findings indicate that drought stress significantly alters micro- and macromolecular metabolism in soybean plants. Differential responses were observed among roots and leaves as well as drought-tolerant and drought-sensitive cultivars, highlighting the complex interplay between overexpressed transcription factors and drought stress in soybean plants.